Preliminary Study on the Growth Performance of Nile Tilapia (Oreochromis niloticus) in Biofloc Fish Farming - Gurung, Shailesh; Rai, Sunila; Jha, Dilip Kumar; Mandal, Ram Bhajan; Luitel, Himal (Journal of the Institute of Agriculture and Animal Science, 2024)
Globally, Nile tilapia (Oreochromis niloticus) is one of the most farmed fish with a significant contribution in improving local livelihoods, particularly in developing countries. A trial on the growth performance of tilapia in biofloc system was conducted at IAAS, Paklihawa Campus, Bhairahawa, Nepal from 6th July, 2022 to 31st Sept. 2022 upto 90 days. Altogether 15 circular polytank of 500 liter water capacity each were used to conduct the trial with stocking density of 50 fish (0.5 m3). Continuous aeration was supplied by 1 Hp ring blower connected to each tank to facilitate the dissolved oxygen. A trial was set up in a Completely Randomized Design (CRD) with 5 treatments, each replicated thrice. The treatments were: (i) T1-without floc control, (ii) T2-with floc sugar, (iii) T3-with floc corn flour, (iv) T4-with floc rice bran and (v) T5-with floc molasses. Carbon to nitrogen ratio was maintained at 10:1 to ensure the growth and reproduction of heterotrophic microorganisms in biofloc system with locally available carbon sources. Mono-sex tilapia fish seeds with an intitial average weight of 4.05±0.44 g were stocked in each tank and 25% CP based pellet feed prepared in lab was given twice daily at 3% of body weight. Water quality parameters were significantly different (p<0.05) among other treatments except total dissolved solids. There was no significantly different (p<0.05) among the treatments in temperature, dissolved oxygen, pH and ammonia.. Final mean weight, daily weight gain of tilapia was significantly (p<0.05) different among the treatments. The highest Daily Wight Gain was found in T5 (0.40±0.01 (g fish-1d-1) and the lowest was found in T1 (0.18±0.01 (g fish-1d-1). FCR was found better in T4 with 0.96±0.04 and accordingly least performance was recorded in T1 with 1.28±0.10. Gross Fish Yield in T5 (3.9±0.07 kg tank-1) was significantly higher (p<0.05) than T2, T3, T4 and T1 respectively. Similarly, T5 (3.51±0.09 kg m3) was also significantly higher (p<0.05) in extrapolated Net Fish Yield than T2, T3, T4 and T1 respectively. The study reveals that the growth performance of tilapia in T5 incorporated with molasses for floc development, could be a better choice for the growth performance, feed utilization and water quality improvement in biofloc system.